Variation of Desolvation Behavior in Two Isostructural Metal–Organic Frameworks Based on a Flexible, Racemic Bifunctional Organic Linker. Issue 27 (6th August 2016) - Bezrukov, Andrey A.; Törnroos, Karl W.; Dietzel, Pascal D. C.
Abstract : A racemic mixture of the chiral ligand 4, 4′‐(1, 2‐dihydroxyethane‐1, 2‐diyl)dibenzoic acid was used to prepare two isostructural metal–organic frameworks, CPO‐49‐Zn and CPO‐49‐Mn, which contain coordinated solvent molecules at the metal site. The compounds showed different behavior upon desolvation. The dissociation of the solvent molecule from the metal site leads to a single‐crystal‐to‐single‐crystal transformation. In CPO‐49‐Zn, a change of coordination geometry from trigonal bipyramidal to tetrahedral occurs at the zinc atom. In CPO‐49‐Mn, a rearrangement of coordination mode of a carboxylate group occurs instead, leading to a 4+1 coordination of the manganese cation in the form of a capped distorted tetrahedron. N2 gas adsorption confirms that both desolvated structures are permanently porous. The behavior of the compounds upon heating has also been studied using variable temperature powder X‐ray diffraction. The presence of a coordinated solvent molecule in the as‐synthesized structures indicates the possibility to access the metal cation with reactive substrates. Both materials were evaluated in the catalytic oxidation of styrene. CPO‐49‐Mn showed significantly higher conversion than the CPO‐49‐Zn material. Abstract : Two new isostructural metal–organic frameworks based on Zn and Mn and a chiral organic linker were synthesized. Solvent removal leads to single‐crystal‐to‐single‐crystal transformation, which proceeds in different fashion for the two metals. The compounds also behave differently upon heating and in catalysis.